DETERMINAN LINGKUNGAN DAN PERILAKU BERHUBUNGAN DENGAN TERJADINYA PENYAKIT INFEKSI TOXOPLASMOSIS DI WILAYAH KOTA SEMARANG - Novia Aditama (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
WHO’s record in 2012 said that at least 1/3 to 1/2 of world population (around 2 billion people) endure to toxoplasmosis. In Indonesia toxoplasmosis prevalence estimated around 2%-88%. By now, In Semarang city, reported that toxoplasmosis occurrence are fluctuate but tend to increase every year. Until the end of 2015, the number of toxoplasmosis case in Semarang city that have been reported are 54 cases. The purpose of this research is to investigate environment and behavior determinant which related to the toxoplasmosis infection disease occurrence in Semarang city.This research is a quantitative analytical research that using case-control research design. The sampling technique that used is proportional cluster random sampling and the total sample in this study are 56 samples. The bivariate analysis result shows that variable that related to toxoplasmosis infection in Semarang city is the habit of consuming raw meat or half-cooked meat (p=0,003£0,05; OR=5,667). Therefore, people are expected to intensify act that prevent the toxoplasmosis infection by behaving a clean and healthy life, and also health institution do a controlling and preventing action of toxoplasmosis by educate, socialize, counseling, and health promotion so that people can prevented from toxoplasmosis.